Pancasila dalam Dunia Pendidikan yang Berdampak pada Dunia Politik - Juariyah, Juariyah; Adhaini, Dina; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Pancasila, as the basis of the Indonesian state, has a very important role in education and politics. Pancasila-based education aims to shape the character and identity of the nation by instilling national, moral, and democratic values from an early age. Through this education, the young generation is not only taught about academic knowledge, but also about the importance of unity, social justice, and participation in the life of the nation and state. Pancasila education has a significant impact on increasing the political awareness of the younger generation, which plays an active role in maintaining Indonesia's political stability. The application of democratic values in education also contributes to the development of positive attitudes towards the political system and government. Thus, Pancasila education is one of the main pillars in strengthening Indonesia's social and political stability. This study aims to analyze the role of Pancasila education in building political awareness of the younger generation and its impact on Indonesian politics, as well as to explore the importance of Pancasila education in maintaining the integrity of the nation in the midst of the era of globalization.